Modulation of the Microstructure and Enhancement of the Photocatalytic Performance of g-C3N4 by Thermal Exfoliation - Zhao, Xinshan; Yu, Junwei; Meng, Tingyu; Luo, Yuanyuan; Fu, Yanzhen; Li, Zhao; Tian, Lin; Sun, Limei; Li, Jing (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2024)
This work explores the impact of reaction temperature during thermal exfoliation treatment of bulk-g-C3N4 in the air atmosphere on the structure and performance of the resulting CN photocatalyst. The analysis conducted using XRD, FT-IR, XPS, SEM, and elements mapping tests, illustrated an increase in nitrogen-vacancy and oxygen content on the surface of the CN photocatalyst, resulting in a porous and sparse structure, changes in crystal size, and improved visible light absorption performance. The photocatalytic reduction experiments of hexavalent chromium (Cr(VI)) showed that the CN-540 showed the highest reduction rate of 96.9%, with a reaction rate constant 6.21 times that of bulk-g-C3N4. After 100 min of illumination, the photocatalytic degradation rates of CN-540 for TC-HCl and RhB were 66.7% and 60.6%, respectively. The TOC test results indicated mineralization rates of 51.5% for TC-HCl and 46.6% for RhB. Room temperature fluorescence spectroscopy (PL), transient photocurrent response (TPC), and electrochemical impedance spectroscopy (EIS) measurements confirmed the excellent photogenerated charge carrier separation and transport efficiency of CN-540. The photocatalytic mechanism for reducing Cr(VI) by CN-540 was elucidated based on the active species •OH and •O2– and Mott-Schottky (M-S) tests. This study provides experimental data for optimizing the photocatalytic performance of g-C3N4 and paves a new way for developing efficient photocatalysts. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).